Blood mineral profile of the critically endangered Western Derby eland (Taurotragus derbianus derbianus) in two conservation breeding reserves in Senegal - Stoklasová, Lucie; Váhala, Jiří; Hejcmanová, Pavla (Journal of animal physiology and animal nutrition, 2021)
For many nondomestic species, nutritional requirements and the challenges faced in their current habitats are unknown. This is the case of small semi-captive population of the critically endangered Western Derby eland held in two wildlife reserves (the Bandia and the Fathala) in Senegal. The aim of this study was to determine the mineral profile (Ca, P, Mg, Cu, Fe, Zn, Se, K, S) in blood serum and to identify potential mineral deficiencies. Serum data (11 individuals) were compared to other Tragelaphineae, where it was lower in almost all elements. Considerably low concentrations were recorded for Cu, Fe and Zn. Animals in the Bandia reserve had higher serum levels of Fe and K compared to the Fathala reserve and a higher serum level of S in the Fathala reserve compared to the Bandia reserve. Recorded mineral levels may reflect most likely the limited mineral background in the local environment. The knowledge of adequate nutritional requirements and health status of these animals is relevant for the conservation breeding programme. No other serum mineral reference values exist for Western Derby eland, neither for free-ranging nor captive animals. Therefore, the knowledge of reference intervals for minerals in serum may serve for monitoring of the population's health.
Keywords: Senegal; minerály; nutriční nároky; Animals; Minerals; West Africa; divoká zvířata; antelope; zvířata; Antelopes; ruminant; Nutritional Requirements; antilopy; Animals, Wild; mineral nutrition; blood serum biochemistry